Evaluating Chagas disease progression and cure through blood-derived biomarkers: a systematic review. Issue 9 (September 2013) - Requena-Méndez, Ana; López, Manuel Carlos; Angheben, Andrea; Izquierdo, Luis; Ribeiro, Isabela; Pinazo, Maria-Jesús; Gascon, Joaquim; Muñoz, José
This article reviews the usefulness of various types of blood-derived biomarkers that are currently being studied to predict the progression of Chagas disease in patients with the indeterminate form, to assess the efficacy of antiparasitic drugs and to identify early cardiac and gastrointestinal damage. The authors used a search strategy based on MEDLINE, Cochrane Library Register for systematic review, EmBase, Global Health and LILACS databases. Out of 1716 screened articles, only 166 articles were eligible for final inclusion. The authors classified the biomarkers according to their biochemical structure and primary biological activity in four groups: i) markers of inflammation and cellular injury, ii) metabolic biomakers, iii) prothrombotic biomarkers and iv) markers derived from specific antigens of the parasite. Several potential biomarkers might have clinical potential for the detection of early cardiopathy. Such capacity is imperative in order to detect high-risk patients who require intensive monitoring and earlier therapy. Prospective studies with longer follow-ups are needed for the appraisal of biomarkers assessing clinical or microbiological cure after therapy. At the same time, studies evaluating more than one biomarker are useful to compare the efficacy among them given the lack of a recognized gold standard.